MAPK-targeted therapies in non-gastrointestinal stromal tumor soft tissue sarcomas: current landscape and future directions - Al Jarroudi, Ouissam; El Bairi, Khalid; Brahmi, Sami Aziz; Afqir, Said (Frontiers in Oncology, 2025)
Non-Gastrointestinal Stromal Tumors (Non-GIST) Soft Tissue Sarcomas (STS) are highly aggressive and challenging diseases with poor prognosis and limited therapeutic options. Molecular profiling is urgently required to gain a deeper understanding of STS pathogenesis and to identify a comprehensive landscape of genomic alterations in order to develop effective targeted therapies. The mitogen-activated protein kinase (MAPK) signaling pathway is a key molecular mechanism involved in sarcoma development. This study aims to conduct a literature review on the involvement of the MAPK cascade in non-GIST STS, with a focus on the role of MAPK inhibitors in the current treatment paradigm for STS. Furthermore, recent data have provided promising preliminary findings regarding the use of new molecular agents targeting the MAPK pathway, either as single therapies or in combination with other drugs. Numerous clinical trials are currently ongoing, and their outcomes are eagerly awaited. Further research is required in both translational and clinical settings to molecularly characterize STS, identify novel causal alterations, accelerate target discovery, and identify potential biomarkers. Moreover, the development of novel nanomaterials provides a promising perspective that may lead to significant advancements in clinical practice.